How does the knowledge level of physicians and nurses working at primary health centers affect their preference for oral contraceptives in an inland Turkish province? - Gamze Dur; Ayşen Mert; Rıza Dur; Mine Kanat Pektas (BMC Primary Care)
Abstract Background Standardizing the knowledge of health care givers and eliminating their misconceptions would help to achieve optimal service for contraception. This study aims to evaluate the knowledge levels of physicians and nurses working at primary health care centers about the oral contraceptive pill (OCP) use. Methods This is a cross-sectional review of 306 professional care givers (117 physicians and 189 nurses) who are working at primary health care centers. Results Only 17.3% of health care givers recommend OCP as their first professional choice of contraception for their patients. Approximately 50.3% of these care givers do not feel qualified about the OCPs and 81.7% of them wish to have regular training about OCPs. There is a significantly higher number of male health care givers who claim that OCPs cause acne, sexual dysfunction, ectopic pregnancy, deep vein thrombosis, and liver cancer (respectively p = 0.040, p = 0.028, p = 0.001, p = 0.001, and p = 0.020). When compared to nurses, there is a significantly higher number of physicians who state that OCPs cause acne, depression, sexual dysfunction, ectopic pregnancy, deep vein thrombosis, breast cancer and liver cancer. Conclusion Physicians and nurses working at primary health centers in an inland Turkish province have relatively lower rates of recommendation for OCP use. These lower recommendation rates become significantly more obvious in male physicians with ≥ 14 years’ experience. The concern about probable adverse effects, the lack of standardization in formal education, the absence of post-graduate training and the shortage of time and resources for counseling might have led to the limitation in OCP use.